2008 IEEE Asia-Pacific Services Computing Conference 2008
DOI: 10.1109/apscc.2008.100
|View full text |Cite
|
Sign up to set email alerts
|

An Efficient Rekeying Scheme for Multicast and Broadcast (M&B) in Mobile WiMAX

Abstract: Mobile WiMAX (IEEE 802.16e) is an emerging technology for wireless broadband access network. It provides wider converge and higher bandwidth than conventional wireless technologies. Multicast and Broadcast (M&B) in WiMAX are suitable for multimedia applications such as Pay-TV system because multimedia providers can efficiently distribute the same contents to the users within the same M&B group. Although IEEE 802.16e has defined Multicast/Broadcast Rekeying Algorithm (MBRA) to secure M&B, recent research indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Both keys are used to ensure the forward and backward secrecy based on their lifetime. But in [3], [8] and [9], the authors have shown that the MBRA fails to ensure forward and backward secrecy. Also the MBRA is not scalable for large group as the message complexity is O(n), which means that it increases proportionally with the number of group members, n. Scalable multicast key distribution and group key management protocols specification are amongst few works in secure multicast and broadcast [3] [8].…”
Section: Related Workmentioning
confidence: 99%
See 3 more Smart Citations
“…Both keys are used to ensure the forward and backward secrecy based on their lifetime. But in [3], [8] and [9], the authors have shown that the MBRA fails to ensure forward and backward secrecy. Also the MBRA is not scalable for large group as the message complexity is O(n), which means that it increases proportionally with the number of group members, n. Scalable multicast key distribution and group key management protocols specification are amongst few works in secure multicast and broadcast [3] [8].…”
Section: Related Workmentioning
confidence: 99%
“…16 network, that works in O(1) constant time complexity. Their scheme is based on LORE, as proposed in [9], a linear ordering key distribution algorithm that can handle forward and backward secrecy.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations